Multicenter Clinical Investigation of a New Active Osseointegrated Steady-State Implant System. Issue 9 (October 2020) - Mylanus, Emmanuel A. M.; Hua, Håkan; Wigren, Stina; Arndt, Susan; Skarzynski, Piotr Henryk; Telian, Steven A.; Briggs, Robert J. S.
Abstract : Objective: A new active transcutaneous bone conduction hearing implant system that uses piezoelectric technology has been developed: an active osseointegrated steady-state implant system (OSI). This was the first clinical investigation undertaken to demonstrate clinical performance, safety, and benefit of the new implant system. Study Design and Setting: A multicenter prospective within-subject clinical investigation was conducted. Patients: Fifty-one adult subjects with mixed and conductive hearing loss (MHL/CHL, n = 37) and single-sided sensorineural deafness (SSD, n = 14) were included. Main Outcome Measure: Audiological evaluations included audiometric thresholds, speech recognition in noise, and quiet. Hearing and health-related patient-reported outcomes (PROs; health utilities index [HUI], abbreviated profile of hearing aid benefit [APHAB], and speech, spatial of qualities of hearing scale [SSQ]), daily use, surgical and safety parameters were collected. Results: Intra- and postoperative complications were few. One implant was removed before activation due to post-surgical infection. Compared with the preoperative softband tests, a significant improvement in speech recognition-in-noise was observed in the MHL/CHL group (–7.3 dB, p ⩽ 0.0001) and the SSD group (–8.1 dB, p = 0.0008). In quiet, word recognition improved in the MHL/CHL group, most markedly at lower intensity input of 50 dB SPL (26.7%, p ⩽ 0.0001). The results of all PROs showed a significant improvement with the new device compared with preoperative softband in the MHL/CHL group. In the SSD group significant improvements were observed in the APHAB and SSQ questionnaires. Discussion: The results confirmed the clinical safety, performance, and benefit of this new treatment modality for subjects with CHL, MHL, and SSD.